La servitude de lignes téléphoniques : une incongruité juridique tenace - Normand, Sylvio (Les Cahiers de droit, 1987)
The confusion reigning between superficies ownership and real servitude is tenacious. There is one case that illustrates this state of uncertainty better than any other: it involves the difficulty of qualifying networks made up of electric lines, telephone lines and water, gas and drainage conduits. This paper examines a case in which the qualifying of a telephone line was the main point at issue. Both the Superior Court and the Court of Appeal qualified the said line as being a servitude. This author does not accept such qualification. For him, the telephone line is apiece of surface property to which attach accessorily various servitudes.